2020
DOI: 10.18632/aging.102742
|View full text |Cite|
|
Sign up to set email alerts
|

Aucubin exerts anti-osteoporotic effects by promoting osteoblast differentiation

Abstract: Osteoporosis is a metabolic disease characterized by reduced osteoblast differentiation and proliferation. Oxidative stress plays a role in the pathogenesis of osteoporosis. Aucubin (AU), an iridoid glycoside, was previously shown to promote osteoblast differentiation. We investigated the effects of AU on MG63 human osteoblast-like cells treated with dexamethasone (Dex) or hydrogen peroxide (H 2 O 2) to induce oxidative damage. AU protected MG63 cells against apoptosis, and promoted increased expression of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…The osteogenic function of osteoblasts is inhibited by oxidative stress and mitochondrial dysfunction [ 4 , 5 ]. Therefore, we next assessed the effect of PAC on the early differentiation and mineralization of the Dex-treated cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The osteogenic function of osteoblasts is inhibited by oxidative stress and mitochondrial dysfunction [ 4 , 5 ]. Therefore, we next assessed the effect of PAC on the early differentiation and mineralization of the Dex-treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that it can inhibit osteoblast proliferation and promote apoptosis [ 31 , 32 ] by triggering oxidative stress and mitochondrial dysfunction. Li et al found that Dex treatment increased intracellular ROS accumulation as well as the dissipation of MMP in MG63 cells [ 4 ]. The mitochondrial accumulation of ROS induced a vicious cycle of oxidative stress and mitochondrial dysfunction, which culminated in the activation of the apoptotic pathway [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34] Several studies have also demonstrated that antioxidants from plant sources, such as apigenin, curcumin, and aucubin, are able to increase osteoblast viability in many osteoblast cell models, including; Saos-2, MC3T3-E1, and MG-63. [35][36][37] These findings provide support that polyphenols found in the tea likely acted as antioxidants to reduce oxidative stress thus increasing activity and mineralization. More specifically, using the same cell model, researchers have observed both elevated cell activity and mineralization in response to tea (black, green, and rooibos).…”
Section: Discussionmentioning
confidence: 58%